2008
DOI: 10.1002/app.27380
|View full text |Cite
|
Sign up to set email alerts
|

The continuous depolymerization of filled polytetrafluoroethylene with a continuous process

Abstract: A new method for beneficiating unfilled as well as filled polytetrafluoroethylene (PTFE) waste has been developed. This process does not use any carrier gas while forming the depolymerization products. It enables polymer manufacturers and end-users to reuse and adds value to filled fluorocarbon polymer waste. The filler material was qualified by means of scanning electron microscopy and thermogravimetric analysis and the success of the depolymerization process inside a rotating kiln was proved by visual observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…7 However, the manufacture of various PTFE products causes the generation of a large amount of waste. [8][9][10] Hence, studies on the degradation of waste PTFE materials are considered a matter of considerable importance. [11][12][13][14][15][16][17] Hlavaty and Kavan found that PTFE could react with alkali metals in organic solvents and produce highly reactive polyynes and metal fluorides.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, the manufacture of various PTFE products causes the generation of a large amount of waste. [8][9][10] Hence, studies on the degradation of waste PTFE materials are considered a matter of considerable importance. [11][12][13][14][15][16][17] Hlavaty and Kavan found that PTFE could react with alkali metals in organic solvents and produce highly reactive polyynes and metal fluorides.…”
Section: Introductionmentioning
confidence: 99%
“…[555] Continuous depolymerization was demonstrated for filled PTFE. [556,557] As polyolefins are inert, their back-to-monomer recycling is challenging. State-of-the-art thermal cracking of polyolefins produces complex mixtures of low-molecular-weight alkanes and alkenes together with aromatics that require separate refining, to convert pyrolysis oil into olefin monomers.…”
Section: Back-to-monomer Molecular Recyclingmentioning
confidence: 99%
“…Likewise with NRe, if NRe ≥ 2000 it will cause the flow to become turbulent so that the previously formed flocs will break and it becomes difficult to settle in the settling zone of the sedimentation unit. According to Van der Walt (2008), flow conditions must be considered to obtain an effective settling velocity. The settling of solid particles and their removal efficiency depends on the flow conditions.…”
Section: Introductionmentioning
confidence: 99%